2018
DOI: 10.1111/jop.12739
|View full text |Cite
|
Sign up to set email alerts
|

Impact of systemic sclerosis oral manifestations on patients’ health‐related quality of life: A systematic review

Abstract: This systematic review demonstrates a correlation between oropharyngeal manifestations of systemic sclerosis and impaired quality of life, despite the low level of evidence of included studies. Large-scaled studies are needed to provide stronger evidence of this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 47 publications
(148 reference statements)
2
30
1
Order By: Relevance
“…Approximately 90% of patients with SSc have a variety of orofacial features such as the fibrosis of the facial skin, microstomia, salivary gland dysfunction and xerostomia, dysphagia as well as an increased risk of dental caries and periodontal disease 4 . A recent systematic review has demonstrated a correlation between orofacial features of SSc and impaired quality of life of patients with SSc 5 …”
Section: Introductionmentioning
confidence: 99%
“…Approximately 90% of patients with SSc have a variety of orofacial features such as the fibrosis of the facial skin, microstomia, salivary gland dysfunction and xerostomia, dysphagia as well as an increased risk of dental caries and periodontal disease 4 . A recent systematic review has demonstrated a correlation between orofacial features of SSc and impaired quality of life of patients with SSc 5 …”
Section: Introductionmentioning
confidence: 99%
“…Dysbiosis of the oral microbiome [3][4][5][6] and host responses influenced by many factors are involved in the pathogenesis of periodontitis [7][8][9][10][11]. Further, presence of systemic diseases [12,13] and gene polymorphisms [14][15][16] are reportedly correlated with the risk for periodontitis. Degradation of extracellular matrix (ECM) within the gingival connective tissue located between tooth and alveolar bone is the driving force in the pathological process of periodontitis [9,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the rarity of SSc, large-scale studies and quantitative analysis were still needed. [5] The biological plausibility for the association between SSc and oral disorders has been revealed by studies [6]. Additionally, multiple comparative studies have been conducted to investigate the possible links between SSc and oral manifestations, however, the ndings were inconsistent [3,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%